Enhanced Neuroplasticity by the Metabolic Enhancer Piracetam Associated with Improved Mitochondrial Dynamics and Altered Permeability Transition Pore Function - Carola Stockburger; Davide Miano; Thea Pallas; Kristina Friedland; Walter E. Müller (Neural Plasticity)
The mitochondrial cascade hypothesis of dementia assumes mitochondrial dysfunction leading to reduced energy supply, impaired neuroplasticity, and finally cell death as one major pathomechanism underlying the continuum from brain aging over mild cognitive impairment to initial and advanced late onset Alzheimer’s disease. Accordingly, improving mitochondrial function has become an important strategy to treat the early stages of this continuum. The metabolic enhancer piracetam has been proposed as possible prototype for those compounds by increasing impaired mitochondrial function and related aspects like mechanisms of neuroplasticity. We here report that piracetam at therapeutically relevant concentrations improves neuritogenesis in the human cell line SH-SY5Y over conditions mirroring the whole spectrum of age-associated cognitive decline. These effects go parallel with improvement of impaired mitochondrial dynamics shifting back fission and fusion balance to the energetically more favorable fusion site. Impaired fission and fusion balance can also be induced by a reduction of the mitochondrial permeability transition pore (mPTP) function as atractyloside which indicates the mPTP has similar effects on mitochondrial dynamics. These changes are also reduced by piracetam. These findings suggest the mPTP as an important target for the beneficial effects of piracetam on mitochondrial function.